Foreign Direct Investments, Institutional Framework and Economic Growth - Arshad Hayat (Charles University in Prague, Institute of Economic Studies (IES), 2017)
This paper explores the role of institutional quality in economic growth and more specifically the role it plays via the channel of foreign direct investments. This paper uses economic performance-relevant indicators of institutional quality (both an aggregated variable of institutional quality and individual indicators) to evaluate their direct impact on economic growth and their indirect impact on economic growth via foreign direct investments. This paper uses a larger dataset of 104 countries and applies GMM estimation method to a dynamic panel data and finds that FDI inflows cause stronger economic growth in countries with better institutional quality compared to countries with lower institutional quality. The same is true for individual institutional quality measure.
Keywords: F23; F43; E23; 330; foreign direct investments; institutional quality; economic growth; GMM